Outsourcing of service areas as a method of increasing the effectiveness of a company - Marek Ziółkiewicz (e-Finanse: Financial Internet Quarterly, 2011)
An increasing number of companies, in order to improve their competitive stance on the market, decide to outsource some of their service functions to external subjects. Outsourcing of this type of activity is frequently regarded as a strategic decision. A properly conducted outsourcing project may considerably improve the operational effectiveness of an enterprise by allowing it to focus on its core competencies. Cooperation with external service providers also enables the enterprise to access professional and often unique knowledge and technology as well as a broad pool of talents. In spite of unquestionable benefits resulting from outsourcing service areas, we should be careful and analyze thoroughly all aspects of the SLA (Service Level Agreement) Contract in order to avoid the pitfalls awaiting inexperienced managers.
Keywords: M10; M14; M20; 330; outsourcing; BPO; strategic management; SSC